Trade and Unions: Can Exporters Benefit from Collective Bargaining? - Stella Capuano; Andreas Hauptmann; Jans-Jörg Schmerer (Center for Economic Studies and ifo Institute (CESifo), 2014)
Unions are often stigmatized as being a source of inefficiency due to higher collective bargaining outcomes. This is in stark contrast with the descriptive evidence presented in this paper. Larger firms choose to export and are also more likely to adopt collective bargaining. We rationalize those stylized facts using a partial equilibrium model that allows us to evaluate firms' value functions under individual or collective bargaining. Exporting further decreases average production costs for large firms in the collective bargaining regime, allowing them to benefit from additional external economies of scale due to lower bargaining costs. Our findings suggest that the positive correlation between export status and collective bargaining can be explained through size. Including controls for firm-size destroys the estimated positive relationship between export status and collective bargaining. Using interaction terms between size and the export status, we find that larger exporters tend to do collective bargaining, whereas smaller exporters tend to refrain from collective agreements.
Keywords: F16; J51; E24; J30; 330; trade; unions; exports; firm level data